Effect of the Apple Cider Vinegar on Weight Management, Blood Glucose Levels and Lipid Profile among Obese/Overweight Adults: A Randomised Control Trial - Ayesha Khalid, A.S Khalid, Eisha Ashiq, Ahtisham (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objectives of this study are to evaluate the effect of apple cider vinegar on weight management, blood sugar level, HbA1C, and on lipid profile. Design: It was a randomized control trial. Study Settings: This study was conducted at OPD of Medicine, Hameed Latif Hospital. Material and Methods: Two groups were formed, each with at least 30 participants. The first group of 30 obese/overweight patients received 15ml of ACV twice a day, before lunch and dinner (total dose of 30ml). The second group was the control group, which received 15ml of ACV twice daily before lunch and dinner (for a total dose of 30ml), but they were healthy and free of disease. The results of both interventional groups (pre and post interventional) in terms of lowering blood glucose and cholesterol levels, as well as body weight, were compared. Results: Both the groups had 15 male and 15 female patients with age of obese and non-obese patients was 43 & 32.5 years respectively. Results showed reduction in weight of obese/overweight patients as compared to day 0 (34.35±6.07), day 30 (33.64±5.99) and day 60 (32.98±5.97), showing consistent reduction in BMI which reflected that increase in time of feeding ACV continued to decrease the body weight of obese/overweight patients. Conclusion: In conclusion it was noted from the results that Apple Cider Vinegar has a positive effect n reducing HbA1c, cholesterol, triglycerides and BMI levels in the respective patients Keywords: Apple Cider Vinegar, Weight, Blood Glucose Levels, Lipid Profile